Fe‐Doped Polyoxometalate as Acid‐Aggregated Nanoplatform for NIR‐II Photothermal‐Enhanced Chemodynamic Therapy. Issue 9 (17th March 2020) - Shi, Yunhao; Zhang, Jiaojiao; Huang, Han; Cao, Changyu; Yin, Jiajia; Xu, Wenjing; Wang, Wenjun; Song, Xuejiao; Zhang, Yewei; Dong, Xiaochen
Abstract: The combination of reactive oxygen species‐involved chemodynamic therapy (CDT) and photothermal therapy (PTT) holds great promise in enhancing anticancer effects. Herein, a multifunctional Fe‐doped polyoxometalate (Fe‐POM) cluster is fabricated via a simple method. The Fe‐POM can not only be utilized as PTT agents to generate a hyperthermia effect for cancer cell killing under near‐infrared (NIR) II laser (1060 nm) irradiation, but also can be used as CDT agents to convert endogenous less‐reactive H2 O2 into harmful ·OH and simultaneously deplete glutathione for an amplified CDT effect. Notably, the hyperthermia induced by PTT can further enhance the CDT effect, achieving a synergistic PTT/CDT effect. Owing to the self‐assembling properties at lowered pH values, the Fe‐POM exhibits high tumor accumulation as revealed by photoacoustic imaging. More importantly, Fe‐POM enables effective destruction of tumors without inducing noticeable damage to normal tissues under 1060 nm laser irradiation. The work presents a new type of multifunctional agent with high PTT/CDT efficacy, providing promising methods for PTT‐enhanced CDT in a NIR‐II biowindow. Abstract : Fe‐doped polyoxometalate (Fe‐POM), fabricated via a simple method can self‐assemble into large aggregates and exhibit high absorbance in the NIR‐II region in acidic environments. Furthermore, the Fe‐POM can not only participate in the Fenton reaction, but also decrease the glutathione level during the redox reaction cycle. Combined with photothermal therapy, its therapeutic efficiency greatly increases.